The "lazy-V" de-epithelialised turn-over fasciocutaneous flap in the reconstruction of skin defects after tendo Achilles repair - (:unkn) unknown (My University, 1992)
Few methods of closure of skin defects lying over the tendo Achilles have been described. The de-epithelialised turn-over flap is one of them but it cannot be used in the presence of a scar proximal to the defect. We describe a modification ("The Lazy-V") of the de-epithelialised turn-over flap which gives it a rotation arc, thus enhancing the versatility of the procedure. This modification is presented with an illustrative case report and a review of the literature.
Keywords: Adult; Female; Humans; Postoperative Complications; Skin; Surgical Flaps; Necrosis; Rupture; Achilles Tendon; Dermatologic Surgical Procedures